Optimizing Formal and Non-Formal Education in Butuh Village, Kalikajar, Wonosobo: A Case Study on Balancing Religious Education and Formal Schools - Amalia Putri, Riza Qori; Candra, Riko Purnama; Widiaji, Kurniawan; Fajarsari, Amalia; Dharmaputri, Indriyani; Vadisa, Vadisa; Prastyanti, Shinta; Runtiko, Agus Ganjar (Technium Sustainability, 2024)
This research explores the balance between formal and informal education in Butuh Village, Kalikajar, Wonosobo, focusing on children’s interest in religious education compared to formal education. Using a qualitative approach with participatory observation and Focus Group Discussions (FGD), this study involved village government, community organizations, educators, community leaders, and Community Learning Centers (PKBM) as informants. The findings indicate a high interest among children in religious education, strong parental and community roles, and challenges in developing formal education, such as limited facilities. Based on the FGD results, programs are proposed for integrating religious values into the formal curriculum, enhancing the role of parents and the community, developing educational infrastructure, and empowering teachers. This research underscores the importance of involving all educational stakeholders in creating sustainable solutions to improve education quality and comprehensively optimize children’s potential. Keywords. Formal Education, Informal Education, Religious Education